COMPULSORY NOTIFICATION AS AN INSTRUMENT OF COMBAT VIOLATION OF THE RIGHTS OF THE CHILD (CIPEEX, 2022)
INTRODUCTION:VIOLENCE AGAINST CHILDREN IS AN IMPORTANT GLOBAL PUBLIC HEALTH PROBLEM WHOSE COMPLEXITY IS AN IMMEASURABLE CHALLENGE, TRIGGERING NEGATIVE IMPACTS ON THE GROWTH AND DEVELOPMENT OF THE VICTIMIZED CHILD. THE WORLD HEALTH ORGANIZATION (WHO) DEFINES VIOLENCE AS ALL FORMS OF MALTREATMENT INVOLVING PHYSICAL, SEXUAL, PSYCHOLOGICAL, AND NEGLECT ABUSE THAT MAY RESULT IN HARM TO THE CHILD'S HEALTH, WHETHER ACTUAL OR POTENTIAL (KRUG ET AL., 2002). FACED WITH THE RECOGNITION OF VIOLENCE AS A PUBLIC HEALTH PROBLEM, THE MINISTRY OF HEALTH HAS MADE VIOLENCE AN OBLIGATORY REPORT (BRAZIL, 2014). OBJECTIVES: GENERAL: TO EVALUATE THE EPIDEMIOLOGICAL PROFILE OF VIOLENCE AGAINST CHILDREN IN CASES OF COMPULSORY NOTIFICATION IN THE MUNICIPALITY OF ANÁPOLIS-GO. SPECIFIC: TO CARRY OUT THE SURVEY OF REPORTED CASES OF VIOLENCE AGAINST CHILDREN BY MEANS OF DATA ENTERED INTO THE INFORMATION SYSTEM AND NOTIFICATION AGGRAVATIONS (SINAN), IN THE MUNICIPALITY OF ANÁPOLIS-GO, FROM 2010 TO 2016 AND IDENTIFY THE OCCURRENCE DATA SUCH AS GENDER, TYPE OF AGGRESSION, PLACE OF OCCURRENCE AND DEGREE OF KINSHIP OF THE AGGRESSOR. METHODOLOGY: THIS IS A CROSS-SECTIONAL, PROSPECTIVE, DESCRIPTIVE STUDY WITH A QUANTITATIVE APPROACH, BEING THE SAMPLE FOR CONVENIENCE. RESULTS AND DISCUSSION: A TOTAL OF 388 CASES OF VIOLENCE AGAINST CHILDREN WERE REPORTED. SEXUAL AND PSYCHOLOGICAL ABUSE PREVAILED IN FEMALES, WITH RELATIVES, FRIENDS AND ACQUAINTANCES BEING THE MAIN AGGRESSORS. THE PHYSICAL VIOLENCE WAS HIGHLIGHTED IN THE MASCULINE SEX BEING THE MATERNAL FIGURE THE MAIN AGGRESSOR. NEGLIGENCE PRESENTED SIMILAR RESULTS FOR BOTH SEXES. THE INTRA-FAMILY ENVIRONMENT WAS THE PREDOMINANT PLACE FOR VIOLENCE AGAINST CHILDREN. FINAL CONSIDERATIONS: THE IMPACT OF VIOLENCE ON THE CHILD'S LIFE TRIGGERS IMMEASURABLE BIOPSYCHOSOCIAL LOSSES IN THE SHORT AND LONG TERM. THE CHILD HAS AN INALIENABLE RIGHT TO LIFE, DIGNITY AND PROTECTION. BASED ON THIS ASSUMPTION, EACH PROFESSIONAL INDEPENDENT OF THE AREA OF ACTION DEVELOPS THE COMMITMENT TO CREATE ADEQUATE CONDITIONS TO FAVOR THE GUARANTEE OF THIS RIGHT. IN THIS PERSPECTIVE, COMPULSORY NOTIFICATION FOR CASES OF VIOLENCE, IN ADDITION TO PROMOTING SOCIAL, HUMAN AND EPIDEMIOLOGICAL VISIBILITY, ASSISTS IN THE IMPLEMENTATION OF ACTIONS, STRATEGIES AND PUBLIC POLICIES AIMED AT PROMOTING, PREVENTING AND COMBATING VIOLENCE AGAINST CHILDREN IN ALL SPHERES NATIONAL.
Keywords: Child violence. Compulsory notification. Epidemiology